ADTH-02 Trans-anal submucosal endoscopic resection (taser) for complex rectal polyps. (8th June 2018) - Stasinos, Ioannis; Tsiamoulos, ZP; Papastergiou, Vasilios; Rameshshanker, Rajaratnam; Polecina, Adel; Sebastian, Joseph; Wawszczak, Aurelia; Faiz, Omar; Warusavitarne, Janindra; Saunders, BP
Abstract : Introduction: Trans-Anal Submucosal Endoscopic Resection (TASER) is a novel instrumental platform for resection of large (≥5 cm) and/or complex rectal polyps (CRPs). It involves a multi-port trans-anal access, enabling dynamic tissue retraction to assist endoscopic submucosal dissection (ESD), used alone or in conjunction with supplementary techniques [Endoscopic Mucosal Resection (EMR) or Ablation (EMA), Trans-Anal Excision (TAE)]. Methods: A prospective database (Jan 2013–October 2017) was analysed including consecutive patients undergoing TASER for CRPs in two UK centres. Results: Sixty-four CRPs (median size 7.5 cm; range: 5–18) were resected in 64 patients (36 males, mean 67.1 years): 33 by ESD and 31 by hybrid procedures (ESD+EMR=14, ESD+EMR+EMA=6, ESD+TAE=4, ESD+EMR+TAE=3, ESD+EMR+EMA+TAE=4). Forty-seven (73.4%) lesions were granular-type laterally spreading tumors, 9 (14.1%) were recurrences, 13 (20.3%) had severe submucosal fibrosis, and 7 (10.9%) involved the dentate line. Histology showed low-grade adenoma/dysplasia in 35 (54.7%), high-grade adenoma/dysplasia in 21 (32.8%), T1<1000 µm in 5 (7.8%), and T1≥1000 µm in 4 (6.2%). In 10 cases a full-thickness dissection was required due to severe submucosal fibrosis (n=8) or T1 cancer (n=2); the defect was closed in 6/10, by using endoclips (n=2) or surgical sutures/endoclips (n=4). All patients were admitted for overnight observation and intravenous antibiotic cover; the median hospital stay was 1 day (range 1–6). Complete endoscopic excision was achieved in a single session in 60 (93.8%), and 2 sessions in 4 (6.2%) cases. Thirty-eight (59.4%) resections were en-bloc, and 36(56.3%) were histologically complete. Delayed bleeding and post-polypectomy syndrome occurred in 3 (4.7%) and 7 (10.9%) respectively, with no surgical intervention required. One patient underwent a defunctioning ileostomy due to intra-peritoneal perforation. Of the 9 malignant cases: 4 with T1≥1000 µm cancer (2/4 full thickness) were subject to radical surgery, and 5 with T1<1000 µm underwent endoscopic surveillance. Endoscopic surveillance data were available for 44 (68.8%) patients, with a median (range) follow-up of 9.2 (3–43.5) months. The local recurrence was 13.6%; in all cases treated endoscopically. To date, the overall rate of patients spared from radical surgery is 60/64 (93.7%). Conclusions: The current study demonstrates favorable clinical outcomes of TASER, offering surgery-sparing cure in >90% of patients with CRPs. The use of a transanal platform to allow a flexible resection approach, enabling both endoscopic and trans-anal resection techniques, appears to be advantageous.